Green synthesis, characterisation and antibacterial activities of Strobilanthes crispus-mediated silver nanoparticles (SC-AGNPS) against selected bacteria - Rohazila Mohamad Hanafiah; Siti Aisyah Abd Ghafar; Vuanghao Lim; Siti Nor Asma Musa; Fahmi Yakop; Arif Haikal Hairil Anuar (Informa UK Limited, 2024)
Indexed by WOS/Scopus